Effects of policy interventions on the introduction of novel oral anticoagulants in Stockholm: an interrupted time series analysis - Komen, Joris; Forslund, Tomas; Hjemdahl, Paul; Andersen, Morten; Wettermark, Björn (British journal of clinical pharmacology, 2017)
Aims The aim of the present study was to assess the effect of policy interventions – i.e. reimbursement decisions, guidelines and regional recommendations – on the prescribing of oral anticoagulant treatment in patients with atrial fibrillation (AF). Methods Interrupted time series analyses were carried out using monthly data on all patients with a recorded diagnosis of AF newly initiated (switchers and anticoagulant‐naïve patients alike) on warfarin, dabigatran, rivaroxaban or apixaban in the Stockholm region from April 2011 until February 2016. Results A total of 34 165 initiations in 27 942 patients were included. The publication of the European Guidelines was associated with an increase in novel oral anticoagulant (NOAC) initiations of 12.5% [95% confidence interval (CI) 7.3, 17.7] after 5 months. The choice between the different NOACs was mainly associated with changes in the regional recommendations, with apixaban initiations increasing by 19.5% (95% CI 16.3, 22.7) 5 months after the drug was recommended as a first‐line alternative to warfarin. Dabigatran received a second‐line recommendation but initiations decreased by −9.5% (95% CI −12.6, –6.4), and initiations of rivaroxaban, which had no specific recommendation, decreased by −9.2% (95% CI −12.7, –5.7). A steady decrease in warfarin and increase in NOAC initiations was seen throughout the study period and from November 2015, AF patients were more likely to receive apixaban than any other anticoagulant, while less than 20% of the initiations were with warfarin. Conclusions After reimbursement and inclusion in the European guidelines, the NOACs started gaining in popularity, while changes in regional recommendations were associated with the biggest change in prescribers’ choice between the different NOACs.